Mental health need of students at entry to university: Baseline findings from the U‐Flourish Student Well‐Being and Academic Success Study. Issue 2 (11th February 2020) - King, Nathan; Pickett, William; McNevin, Steven H.; Bowie, Chris R.; Rivera, Daniel; Keown‐Stoneman, Charlie; Harkness, Kate; Cunningham, Simone; Milanovic, Melissa; Saunders, Kate E. A.; Goodday, Sarah; Duffy, Anne; et al.
Abstract: Aim: Transition to university is associated with unique stressors and coincides with the peak period of risk for onset of mental illness. Our objective in this analysis was to estimate the mental health need of students at entry to a major Canadian university. Methods: After a student‐led engagement campaign, all first year students were sent a mental health survey, which included validated symptom rating scales for common mental disorders. Rates of self‐reported lifetime mental illness, current clinically significant symptoms and treatment stratified by gender are reported. The likelihood of not receiving treatment among those symptomatic and/or with lifetime disorders was estimated. Results: Fifty‐eight per cent of all first‐year students (n = 3029) completed the baseline survey, of which 28% reported a lifetime mental disorder. Moreover, 30% of students screened positive for anxiety symptoms, 28% for depressive symptoms, and 18% for sleep problems with high rates (≅45%) of associated impairment. Only 8.5% of students indicated currently receiving any form of treatment. Females were more likely to report a lifetime diagnosis, anxiety and depressive symptoms, as well as current treatment. Over 25% of students reported lifetime suicidal thoughts and 6% suicide attempt(s). Current weekly binge drinking (25%) and cannabis use (11%) were common, especially in males. Conclusions: There is limited systematically collected data describing the mental health needs of young people at entry to university. Findings of this study underscore the importance of timely identification of significant mental health problems as part of a proactive system of effective student mental health care.